PENERAPAN SISTEM MANAJEMEN PESERTA DIDIK DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SDN 120/II PULAU JELMU KECAMATAN JUJUHAN KABUPATEN MUARA BUNGO PROVINSI JAMBI - Rinja Yurhanif; Elvi Syoviana; Lesis Andre; Afriwes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research highlights the importance of discipline as a key pillar inshaping students’ character from an early age. At SDN 120/II Pulau Jelmu, studentdiscipline is a major focus, particularly in attendance, compliance with schoolrules, and responsibility in completing assignments. An effective studentmanagement system is viewed as a strategic solution to enhance discipline.Thestudy aims to describe how the implementation of a student management systemcan improve discipline at SDN 120/II Pulau Jelmu. Using a qualitative descriptiveapproach, data were collected through observation, interviews, anddocumentation. Research subjects included 17 students, class teachers, andseveral parents. Findings show that the student management system effectivelyimproves discipline in line with its planned implementation. Teacher and staffinvolvement plays a significant role in fostering discipline, supported by highattendance rates: 98.82% (84 out of 85 school days), with 94.12% (16 of 17students) present for all five days each week, and only 5.88% (1 of 17 students)absent without explanation. These results indicate excellent attendance and reflectstrong discipline in school presence.Overall, the system functions well and meetsits objectives. The study concludes that a well-planned student managementsystem, involving teachers, parents, and staff, can significantly improve discipline.Consistent school support and strong communication between school and homeare crucial for sustaining these results.